Dietary supplements usage by elite female football players: an exploration of current practices. (20th June 2021) - Oliveira, Catarina B.; Sousa, Mónica; Abreu, Rodrigo; Ferreira, Ângela; Figueiredo, Pedro; Rago, Vincenzo; Teixeira, Vitor Hugo; Brito, João
Abstract : The present study aimed to investigate the prevalence of dietary supplements usage (types, reasons for usage, sources of information, purchase venues) among elite female football players, using a self‐administered questionnaire. The study participants ( n  = 103) were recruited through team physicians during an official international tournament. Overall, 82% reported using dietary supplements at least once during the last 12 months. The most common dietary supplements were vitamin D (52%), omega‐3 fatty acids (49%), and protein (45%). Primary reasons for dietary supplement use were to stay healthy (66%), to accelerate recovery (58%), and to increase energy/reduce fatigue (54%). Supplement advice came mainly from medical doctors (46%), dietitians/nutritionists (43%), and coaches/fitness coaches (41%). Most dietary supplements were acquired from supplement stores (30%), a sponsor (26%), or drugstores/pharmacies (22%). Elite female football players are frequent dietary supplement users. Further research needs to explore the frequency, dose, and timing of these supplements.